2000
DOI: 10.1046/j.1365-2796.2000.00721.x
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms of the β2‐adrenergic receptor gene (ADRB2) in relation to cardiovascular risk factors in men

Abstract: Objective. To investigate the effect of polymorphisms in codon 16 (Arg16Gly) and codon 27 (Gln27Glu) of the b 2 -adrenergic receptor gene (ADRB2) on anthropometric, endocrine, metabolic and haemodynamic variables. Design. A cross-sectional study. Subjects. A subgroup of 284 Swedish men from a population sample of 1040 at the age of 51 years. Main outcome measures. Genotype examination of ADRB2 polymorphisms in codon 16 and codon 27 with polymerase chain reaction and restriction fragment length polymorphism. An… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
1

Year Published

2001
2001
2008
2008

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(31 citation statements)
references
References 26 publications
4
26
1
Order By: Relevance
“…In accordance with other studies that found higher triglyceridaemia in subjects bearing the Glu allele, 13,19,42,43 plasma triglycerides (TG) remained higher in our Glu27Glu group than in the Gln27Gln group throughout the study. On the other hand, the only measured hormone that significantly differed between groups was insulin, which was higher in the Glu27Glu group.…”
Section: Adrb2 Polymorphism and Exercise In Obese Womensupporting
confidence: 93%
“…In accordance with other studies that found higher triglyceridaemia in subjects bearing the Glu allele, 13,19,42,43 plasma triglycerides (TG) remained higher in our Glu27Glu group than in the Gln27Gln group throughout the study. On the other hand, the only measured hormone that significantly differed between groups was insulin, which was higher in the Glu27Glu group.…”
Section: Adrb2 Polymorphism and Exercise In Obese Womensupporting
confidence: 93%
“…An Arg16Gly variant was found to be associated with a significant 1.8-fold increase risk of hypertension. 234 Confirmatory results for this variant have been reported in other populations 235,236 as well as a negative study. 237 Attenuation of the vasodilatory response in humans with the Gly16 allele provides biological plausibility.…”
Section: ␣-Adducin (Add1)supporting
confidence: 73%
“…The β2AR polymorphisms accounted for ∼2% of the observed variation in blood pressure (Bray et al 2000). While results of some groups confirmed the association between the 16Gly allele and blood pressure (Kotanko et al 1997;Rosmond et al 2000;Gratze et al 1999), others found opposite effects, i.e., an association between the 16Arg allele and hypertension (Busjahn et al 2000;Bengtsson et al 2001a,b;Timmermann et al 1998) or no effects at all (Herrmann et al 2002;Kato et al 2001;Xie et al 2000; for a recent meta-analysis see Hahntow et al 2006). Again, differing inclusion of haplotypes, variations in ethnicities and different study designs may contribute to these sobering results.…”
Section: Genetic Variants In β-Adrenoceptor Genesmentioning
confidence: 98%